INTEGRASI PEMBELAJARAN IPAS DALAM KURIKULUM BERBASIS CINTA DI SEKOLAH DASAR - Sri Wahyuni; Sri Wahyu Ningsih; Lefdiana Monica; Frika Fatimah Zahra (CV. Denasya Smart Publisher, 2025)
This study was designed to describe how the teaching of Natural and Social Sciences (IPAS) is implemented based on the Merdeka Curriculum using a Love-Based Curriculum approach at SD Negeri 158 Palembang. The research employed a descriptive qualitative approach involving direct observations, in-depth interviews, and documentation analysis. The findings show that teachers conducted IPAS learning through active interaction, supported by visual aids, exploratory activities, and reflective discussions that were contextualized with students’ daily lives. The Love-Based Curriculum approach was evident in human-centered teaching practices, including empathetic communication, positive reinforcement, the creation of a psychologically safe environment, and respect for diverse learning styles. This approach proved effective in increasing students’ motivation, curiosity, and socio-emotional skills. However, challenges included limited access to digital media and difficulties faced by teachers in adapting to instructional strategies aligned with the Merdeka Curriculum. Ultimately, the integration of IPAS with the Love-Based Curriculum resulted in meaningful, holistic learning experiences focused on character development.